Flora of Bahia: Priva Adans. – Verbenaceae - Lima, Águida de Barros; França, Flávio (SITIENTIBUS série Ciências Biológicas, 2007)
The genus Priva is an important representative of the Flora of Bahia. It is very common in anthropic areas. Historically, only one species has been recognized for the state (P. bahiensis). However, another species (P. lappulacea) was found among the studied materials at Bahian herbaria, which differ from the first one based on fruit morphology. This paper presents both the descriptions and illustrations of these species.